Elemental abundances in marine carbonates from ODP Leg 115 holes (Table 1) - Yun-Gang Liu; Roman A Schmitt (PANGAEA, 1990)
We subjected 18 carbonate samples <1-46 Ma in age from Holes 706A, 707A, 708A, 709C, 710A, and 711A on or near the Mascarene Plateau and Madingley Rise and from Holes 712A, 713A, and 716A on or near the Chagos Bank-Maldives Ridge to instrumental neutron activation analysis to measure 32 major, minor, and trace elements and to determine the Ce anomalies (CeA*) in the carbonates relative to NASC (North American Shale Composite). Five carbonates, 32-46 Ma, yielded an average CeA* value of 0.14 ± 0.05, corrected for small (0.1%-1.8%) detrital clay particulates. This CeA* value is considered to represent the inferred CeA value in the western Indian Ocean during the 32-46-Ma interval and compares to an average CeA value of 0.05 ± 0.02 in the Pacific Ocean during the past ~35 Ma and from 93 to 97 Ma. These inferred CeA values are consistent with the Ce redox formulation proposed previously by the authors, which indirectly relates the CeA of seawater to the pH of the mixed layer. The higher CeA* values of 0.23-0.66 in 11 carbonates, <1-30 Ma, indicate an inhibition of Ce + 3 oxidation to Ce(OH)4 in seawater during this interval. This observation is consistent with an enhanced transport of decayed organic debris into the Indian Ocean from the Himalayan Mountains, thereby providing a more reducing seawater environment. The postulated prominence of the Himalayas at ~30 Ma is consistent with the ODP Leg 116 observations that the voluminous sedimentation rates in the eastern Indian Ocean from the Bengal Fan existed for the past >24 Ma. An accelerated rise of the Himalayas may have commenced ~33-35 Ma.
Supplement to: Liu, Y-G; Schmitt, RA (1990): Cerium anomalies in western Indian Ocean Cenozoic carbonates, Leg 115. In: Duncan, RA; Backmann, J; Peterson, LC; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 115, 709-714, https://doi.org/10.2973/odp.proc.sr.115.180.1990